Indecent theology : theological perversions in sex, gender and politics - Althaus-Reid, Marcella (Routledge, 2000)
Indecent Theology brings liberation theology up to date by introducing the radical critical approaches of gender, postcolonial, and queer theory. Grounded in actual examples from Latin America, Marcella Althaus-Reid's highly provocative, but immaculately researched book reworks three distinct areas of theology - sexual, political and systematic. It exposes the connections between theology, sexuality and politics, whilst initiating a dramatic sexual rereading of systematic theology. Groundbreaking, intriguing and scholarly, Indecent Theology broadens the debate on sexuality.